Director perspectives to equity, access, and inclusion in the school jazz ensemble - de Bruin, Leon R. (Frontiers in Education, 2022)
Arts and culture are increasingly acknowledged as pillars of society in which all of humanity including people who identify as’ LGBTQIA+ can contribute in 21st century society. United Nations and individual country initiatives continue to promote the notion of inclusive, egalitarian values that promote equal access and opportunity to chosen careers and passions. Jazz as an artform has evolved as a form of cultural expression, entertainment, and political metaphor, subject to societal and populist pressures that have created both a canon and popularized history. Jazz education has moved from largely informal to almost wholly formal and institutionally designed methods of learning and teaching. The jazz ensemble or stage band remains an enduring secondary education experience for most students learning jazz today. This qualitative study of music directors investigates their approaches, perspectives and concerns regarding attitudes and practices in the teaching profession, the promoting of inclusive practices, access, and equity, amidst a pervasive masculinized performance and social structure that marginalizes non-male participation. The study provides implications for how jazz education may continue to evolve in both attitude and enlightened access in the education of jazz learners.